Anatomy and ultrasound imaging of the tibial collateral ligament: A narrative review - Ricci, Vincenzo; Mezian, Kamal; Cocco, Giulio; Donati, Danilo; Naňka, Ondřej; Farì, Giacomo; Özçakar, Levent (Clinical anatomy (New York, N.Y.), 2022)
Medial knee pain is commonplace in clinical practice and ultrasound assessment of the tibial collateral ligament-medial meniscus complex is increasingly becoming a valuable examination tool in the outpatient setting. In the pertinent literature, basic sonographic protocols have been proposed to evaluate the medial compartment of the knee joint. Using high-frequency ultrasound probes and high-level ultrasound machines; we matched the histo-anatomical features of the tibial collateral ligament-medial meniscus complex and its different sonographic patterns in physiological/pathological conditions to define a standardized (layer-by-layer) sonographic approach. Moreover, high-sensitive power Doppler assessments have also been performed to evaluate the nearby microcirculation. Modern ultrasound equipment appears to provide optimal "sonographic dissection" of the tibial collateral ligament-medial meniscus complex for its various physiological/pathological patterns. Likewise, high-sensitive power Doppler allows clear visualization of the microcirculation as regards the local ligamentous and capsular structures. In clinical practice, using adequate technological equipment, a detailed sonographic assessment of the tibial collateral ligament-medial meniscus complex can be performed. High-frequency B-mode ultrasound imaging and high-sensitive power Doppler perfusion patterns can be matched/integrated with the clinical findings to optimize the management of patients with medial knee pain.
Keywords: bolest; Pain; knee; ligamentum collaterale tibiale; Knee Joint; Medial Collateral Ligament, Knee; Ultrasonography; ultrasonografie; Humans; menisky tibiální; medial meniscus; tibial collateral ligament; lidé; ultrasound; power Doppler; Menisci, Tibial; kolenní kloub